Tattoo Removal using (1064 nm and 532 nm) Q-Switched Nd: YAG Laser - AL Saad, Athir M.; Abdullah, Abd Alkhaliq S. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: A tattoo is a foreign material implanted into the dermis by needle or some other trauma that results in a visible mark in the skin .either decorative or cosmetic tattoos or may be traumatic tattoos resulting from car accident or iatrogenic tattoos placed in radiation ports. There are many ways for tattoo removal one of them is laser treatment by Q-Switched (1064 nm and 532 nm) Nd: YAG Laser. Objectives: The purpose of this study is to evaluate the efficacy and safety of Q-Switched Nd: YAG (1064 &532 nm) Laser in treatment of tattoos. Patient and Method: Nineteen lesions of tattoo in different body sites in nine patients collected in private plastic surgery clinic in Baghdad from 1st of September 2010 till end of February 2011 treated by QSwitched Nd: YAG Laser with energy density 8.5 J/cm2 and multiple sessions of treatment up to five with to 6weeks interval. Results: The response of tattoo to laser treatment was variable from patient to patient and from session to session of same tattoo. In general the results were encouraging in majority of lesions except in 5 lesions in which ink has been used for tattooing introduced so deep by manual pricking with needle. Conclusion: switch Nd-YAG laser is a safe and effective option for tattoo removal لمقدمة: الوشم عبارة عن مادة غريبة تدخل في أدمة الجلد بواسطة وغز أبرة او أي شدة خارجية اخرى فتنتج علامة في الجلد، وتستخدم لغرض الديكور او الجمالية واحيانا تكون ناتجة عن حادثة طريق واحيانا أخرى نقوم بعمل الوشم لأسباب علاجية مثل تحديد الأماكن المحتاجة الى تسليط علاج أشعاعي. هنالك طرق عدة لأزالة الوشم و واحدة من هذه الطرق هو ازالة الوشم باستخدام كيو سوج (1064نانو متر، 532 نانو متر) اندي ياك ليزر. اهداف الدراسة:- هو تقييم فعالية كيو سوج (1064نانو متر، 532 نانو متر) اندي ياك ليزر في ازالة الوشم ومدى سلامته. ألأساليب :- تسع عشرة حالة وشم في اماكن متعددة لجسم تسعة ذكور تمت معالجتها بكيو سوج (1064نانو متر، 532 نانو متر) اندي ياك ليزر بطاقة 8,5 جول لكل سنتمتر مربع عدة جلسات قد تصل الى خمسة جلسات وبين جلسة واخرى على الاقل ثلاثة اسابيع وقد تصل الى ستة. النتائج:- كانت النتائج متباينة من شخص الى شخص ومن وشم الى وشم لنفس الشخص ومن جلسة واخرى لنفس الوشم , بصورة عامة كانت النتائج مشجعة بأستثناء خمسة حالات كان الوشم فيها قد عمل بواسطة وغز يدوي مع الحبر الملون. الأستنتاج:- ان كيو سوج (1064نانو متر، 532 نانو متر) اندي ياك ليزر فعال وخيار أمين لازالة الوش